Evolving understanding of Guillain-Barré syndrome pathophysiology and the central role of the classical complement pathway in axonal injury - Gorson, Kenneth C. (Frontiers in Neurology, 2025)
Guillain-Barré syndrome (GBS) is a rare, frequently postinfectious neuromuscular emergency and the leading cause of acute paralytic neuropathy worldwide. GBS incidence varies considerably across geographic regions, owing predominantly to different infectious exposures. In GBS, antecedent infection leads to production of immunoglobulin G and immunoglobulin M antibodies that cross-react with the myelin sheath and axons of peripheral nerves. These antibodies activate the classical complement pathway, which plays a key role in peripheral nerve injury regardless of autoantibody binding to myelin or axons as a target. The heterogeneous clinical presentation and progression of GBS symptoms have long been attributed to binary axonal and demyelinating neurophysiologic classifications; however, evolving evidence indicates that these pathophysiologic processes overlap. Intravenous immunoglobulin and plasma exchange, the current standard-of-care therapies in GBS, both reduce autoantibody levels and complement activation, thereby aiming to address this convergence of pathophysiology. However, these therapies only partially decrease antibody levels and complement activity and require extended courses of treatment (5 days for intravenous immunoglobulin and 7–14 days for plasma exchange), limiting their effectiveness in addressing acute neuronal damage during the active phase of disease. Given its evolutionary role in antibody binding and activating the classical complement pathway, the complement component C1q has been proposed as a therapeutic target in GBS. The clinical trial program of the C1q inhibitor ANX005, including placebo-controlled, double-blind phase 1b and phase 3 trials in GBS, provides insight into the pathophysiology of GBS and the efficacy of C1q inhibition regardless of neurophysiologic classification or geographic location.